ANALYSIS OF THE EFFECTIVENESS OF THE SCRUM METHODOLOGY IN AN EMPLOYEE TASK MONITORING APPLICATION - Dama Sukma Kusuma Diwirya; Nissa Almira Mayangky (Jurnal Techno Nusa Mandiri, 2026)
This study evaluates the effectiveness of the Scrum methodology in improving the productivity of IT development teams at PT. Erajaya Swasembada Tbk, focusing on the development of an employee task monitoring application. Using a mixed-methods approach, it combines qualitative insights from interviews and observations with quantitative metrics from Evidence-Based Management (EBM), including Employee Satisfaction, Lead Time, Velocity, and Innovation Rate. The findings show that Scrum significantly enhances team collaboration and transparency, with an average Employee Satisfaction score of 4.19 out of 5 and Velocity exceeding targets in several sprints (e.g., 167.5% in PROD Sprint 7). However, inconsistent Scrum practices and limited inter-team communication remain challenges. This study provides recommendations to optimize Scrum implementation to improve project outcomes.